Climate change and marine and freshwater toxins - Botana, Luis M.; Louzao, M. Carmen; Vilariño, Natalia (De Gruyter, 2021)
"This book compiles studies on the influence of climate change on the spreading of toxin-producing species in aquatic systems. The chemistry and biology of toxin production is revised and an outlook on control and prevention of the toxins' impact on human and animal health is given. Unique compilation on the impact of climate change on marine and freshwater toxins. Explores the implications for drinking water, (sea)food and feed safety. New in the 2nd Edition: additional chapters on cyanobacteria and dinoflagellates."--